THE RELATIONSHIP OFELEMENTS OF THE FISHERIES EXTENSION ACTIVITIESWITH THE FISH FARMER BUSINESS MOTIVATION IN KOTO BARU SUB-DISTRICT DHARMASRAYA REGENCYWEST SUMATRA PROVINCE - Annisa Lady Fajri; Firman Nugroho; Zulkarnain Zulkarnain (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT The research on was conducted in February until March 2019 in Koto Baru sub-District, Dharmasraya Regency, West Sumatra Province.Its was aimed to find out how the elements of the fisheriesextension activities and how thefish farmerbusiness motivation and than how the relationship of elements of the fisheriesextension activities with thefish farmerbusiness motivation. The method used in this study is the survey method which is analyzed using Rank Spearman and the number of respondents in this study were 30 respondents. From the results of the research, it was found that theelements of the fisheries extension activitieswas seen from an indicator of the extension workers, counseling material, a method of counseling, the media counseling, and frequency counseling are categorized efective with a total score2.088, and tofish farmer business motivation was seen from an indicator of motive, expectation, and incentive are categorized high with a total score 1.271. Have a real relationship and significan between elements of the fisheriesextension activities withfish farmer business motivation, relationships real are value a correlation coefficient 0.932**, it means having value the relationship overpowering. Value correlation between elements of the fisheries extension activities with the fish farmer business motivation valuable (+), it means direction relationship parallel, so that it can be concluded that elements of the fisheries extension activities have relationship on the level of the fish farmer business motivation Keywords: Relationship, elements of the extension activities, business motivation, fish farmer.